Transparent constructions: genre translations in building the New India. Issue 6 (2nd November 2022) - Sargent, Adam
ABSTRACT: In the last 30 years global investment in Indian real estate has transformed cities like Delhi. Construction firms attract investors by presenting construction as transparently manifesting vetted architectural plans and agreed upon budgets. This article examines the politics of such performed transparency by focusing on the communicational genres which accompany these urban buildings. The architectural drawing and the contract supported the authority of project managers, and engineers. Yet such genres were only efficacious on the construction site when supported by other genres such as notes and sketches. These genres translated architectural schematics and budgets into the mundane work activities of the site. Produced by subcontractors, these genres shaped the activities of workers – from bending rebar to laying bricks – by framing them as acts of service within relations of patronage. Yet they also supported the authoritative account books filled out by engineers. The genres of the subcontractors translated official forms in ways that enabled the work of construction, while also laying the foundation for their own erasure in the official genres of the measurement and account books. In this way, I argue that techniques of rendering construction transparent actually reproduce the very forms of labor that they seem to supplant.